Fish community in a surf zone of the northern Sicilian coast (Mediterranean Sea): diversity and functional guild composition - ESPOSITO, V.; CASTRIOTA, L.; BATTAGLIA, P.; CONSOLI, P.; ROMEO, T.; SCOTTI, G.; ANDALORO, F. (Mediterranean Marine Science, 2015)
Fish assemblage in a surf zone of the southern Tyrrhenian Sea was investigated for the first time. Samples were collected during four surveys by a modified beach-seine, from June 2005 to May 2006. Overall, 42 species belonging to 19 families were recorded. Among them, Sardina pilchardus showed the highest abundance values, while Mugilids (Oedalechilus labeo and Liza aurata) were the most frequently caught species. The fish community was dominated by pelagic and gregarious species using this habitat as a foraging ground and recruitment area. Juveniles and early adults made up the largest proportion of the ichthyofauna. Fishes inhabiting the surf zone were mainly strictly benthic invertebrate feeders and invertivorous/piscivorous fish; strictly planktivorous were represented by few species but strongly dominant in terms of catch per unit effort; strictly piscivorous fish were poorly represented. Fish composition varied over the study period with the greatest abundance in May and December, and the highest richness and diversity in October.